Effect of Garlic (Allium sativum L.) Bulb Skin Extract on Urea and Creatinine Levels in Alloxan-Induced Hyperglycemia Wistar Rat - Rosyid, Abdur; Wijayanti, Rina; Azizah, Nuzlil Laily Nur (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2016)
Background: Garlic bulb skin extract contains flavonoid, alkaloid, saponin, quinone and polyphenol. Garlic bulb skin is a waste of garlic bulb which has not been optimally used so far for medical purpose. Objective: to discover the influence of garlic (Allium sativum L.) bulb skin extract on urea and creatinine levels in alloxan-induced hyperglycemia wistar rat. Methods: Experimental research using post-test control group design and its statistic analysis using Kruskal Wallis followed with Mann Witney test. The hyperglychemia rat is made by inducing alloxan at a single dose of 160 mg/kg bodyweight (BW) intraperitoneally. The garlic bulb skin extract doses used are 200mg/200gBW, 400mg/200gBW, and 800mg/200gBW for 14 days. The blood is sampled through vena orbitalis which is tested for its urea and creatinine levels.Results: The urea test in hyperglychemia rat administered with 200mg/200gBB garlic bulb skin extract (average urea level 88.87 mg/dL) has no differencce from the negative group (p>0.05), while the 400mg/200gBB and 800mg/200gBB doses (average urea levels 41.86 mg/dL and 41.96 mg/dL) show significant difference (p<0.05). The creatinine test shows significant influence (p<0.05) in extract dose of 400mg/200gBB (average creatinine level 1.16 mg/dL).Conclusion: it can be concluded that garlic bulb skin extract may have some influence in reducing urea level at 400mg/200gBB and 800mg/200gBB doses and creatinine level at 400mg/200gBB dose.